The impact of long-term exposure to ambient air pollution and second-hand smoke on the onset of Parkinson disease: a review and meta-analysis. (February 2020) - Han, C.; Lu, Y.; Cheng, H.; Wang, C.; Chan, P.
Abstract: Objectives: Long-term exposure to particulate and gaseous air pollution (AP) may trigger the development of Parkinson disease (PD), but this association remains controversial. The relationship between second-hand smoke (SS) and PD risk is also inconclusive. We aimed to systematically review epidemiological studies investigating the association between these AP exposures and PD risk. Study design: This was a systematic review and meta-analysis of studies investigating the relationship of ambient AP and SS with PD risk. Methods: PubMed, Embase, Web of Science, Cochrane Library, and Google Scholar databases were searched. We used a random-effects model to derive pooled estimates of relative risk (RR) and corresponding 95% confidence intervals (CIs) per increment in pollutant concentration. The studied AP included particulate matter with aerodynamic diameter <2.5 μm (PM2.5 ), <10 μm (PM10 ), nitrogen dioxides (NO2, NOx ), ozone (O3 ), and carbon monoxide (CO). Results: In total, 21 studies with 222, 051 patients with PD were eligible for inclusion. We found marginally significant increased risk of PD with per 10-μg/m 3 increase in concentration of PM2.5 (RR = 1.08, 95% CI = 0.98–1.19), NO2 (RR = 1.03, 95% CI = 0.99–1.07), and O3 (RR = 1.01, 95% CI = 1.00–1.02). A positive but non-significant association was also detected for CO (RR = 1.32, 95% CI = 0.82–2.11). Furthermore, an inverse PD-SS relationship was noted irrespective of exposure occasions and timing (at home: RR = 0.73, 95% CI = 0.56–0.95; at work: RR = 0.82, 95% CI = 0.57–1.17; in children: RR = 0.91, 95% CI = 0.76–1.08). Both sensitivity and subgroup analyses generated results comparable with those of the overall analyses. Conclusions: Our study suggested that exposure to PM2.5, NO2, and O3 might contribute to higher risk of PD, whereas SS conferring reduced PD risk. Public and environmental health strategies that aim at reducing outdoor AP levels might reduce the burden of PD. More prospective cohort studies with personal exposure measurements are warranted in the future. Graphical abstract: Image 1 Highlights: PM2.5, NO2, and O3 may contribute to higher risk of Parkinson disease. Second-hand smoke conferred reduced risk of Parkinson disease, regardless of exposure occasions and timing. This is the first meta-analysis on the neuroprotective effect of second-hand smoke. This is the most comprehensive review on the relationship between outdoor air pollution and Parkinson's disease.